Menilik Kembali Pemikiran Filosofis Aquinas tentang Harapan - Widyatmoko, Satriyo (Lux et Sal, 2024)
Although Thomas Aquinas' Summa Theologiae is a theological treatise, its approach is fundamentally philosophical, as it employs the dialectical method of Plato and applies the principles of Aristotelian syllogistic logic. A renewed examination of Aquinas' thoughts on Hope, as one of the three Theological Virtues in Summa Theologiae, illuminated by Robert Spitzer's explanation of the various levels of happiness, emphasizes that the fullness of human life, particularly when reaching the highest level of happiness, lies in the relationship with the Transcendentals: Goodness, Beauty, and Love. This implies the necessity of self-transcendence for the realization of a truly fulfilled human existence.